Acoustic Properties of Tea-Leaf Fiber Mixed Polyurethane Composites - KÜÇÜK, HALUK (SAGE PUBLICATIONS LTD, 2012)
Natural tea-leaf fibers were used as reinforcement agents in different polyurethane-based matrixes to improve the sound absorption properties of the composite. Adding tea-leaf-fibers to rigid polyurethane foam demonstrate limited contribution to sound absorption properties of the material. Furthermore, adding tea-leaf-fibers to soft foam results in a significant improvement of sound absorption properties of the composite. In this study herein, the composite including 24% tea-leaf-fibers was observed to provide the best sound absorption coefficient. Additionally, soft foam demonstrates better acoustic properties than rigid foam.
Keywords: Polymer-matrix composites; Tea-leaf; Fibers; Sound absorption; SOUND-ABSORPTION; MECHANICAL-PROPERTIES; FOAM